2016
DOI: 10.3390/ijms17071066
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Effect of Lambertianic Acid by Inhibiting the AR in LNCaP Cells

Abstract: Lambertianic acid (LA) is known to have anti-allergic and antibacterial effects. However, the anticancer activities and mechanism of action of LA have not been investigated. Therefore, the anticancer effects and mechanism of LA are investigated in this study. LA decreased not only AR protein levels, but also cellular and secretory levels of PSA. Furthermore, LA inhibited nuclear translocation of the AR induced by mibolerone. LA suppressed cell proliferation by inducing G1 arrest, downregulating CDK4/6 and cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Decreased AR signaling leads to apoptosis via activation of Caspase-3. 52 This decreased AR signaling might lead to sPTB via apoptosis of the fetal membrane in the placenta. 53 In addition, interactions of IGF1 and AR genes may affect the onset of spontaneous preterm labor.…”
Section: Genome-wide Linkage Studiesmentioning
confidence: 99%
“…Decreased AR signaling leads to apoptosis via activation of Caspase-3. 52 This decreased AR signaling might lead to sPTB via apoptosis of the fetal membrane in the placenta. 53 In addition, interactions of IGF1 and AR genes may affect the onset of spontaneous preterm labor.…”
Section: Genome-wide Linkage Studiesmentioning
confidence: 99%
“…Interestingly, it had been suggested earlier that molecular crosstalk between IGF1R and AR might lead to sPTB 21 . Later studies have shown that a longer polyglutamine chain in the N-terminal transactivation domain of AR hinders transactivation activity 22 resulting in decreased AR signaling which leads to apoptosis via activation of Caspase-3 23 . Since apoptosis in the placenta is involved in sPTB 24 , decreased AR signaling might lead to sPTB via apoptosis in the placenta.…”
Section: Genomic Approaches To Study Sptbmentioning
confidence: 99%
“…Lambertianic acid (LA; Figure 1a), a major component of Pinus koraiensis , was known to have anti-obesity [18], anti-inflammatory [19], and anti-cancer effects [20,21,22]. Nevertheless, the underlying molecular mechanisms of LA were not fully understood in association with STAT3 phosphorylation and RelA/p65 acetylation.…”
Section: Introductionmentioning
confidence: 99%